Historical Background of Medical Rescue Service Development in Rzeszów Region in Years 1948-2015 - Gajdek, Małgorzata; Kwiatkowski, Andrzej; Binkowska-Bury, Monika (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Voivodeship Rescue Service Station (Wojewódzka Stacja Pogotowia Ratunkowego, WSPR) in Rzeszów was the first to be established in Rzeszów Voivodeship (currently Podkarpackie Voivodeship), four years after the World War II. Since that time, in Rzeszów as well as in the whole region a laborious yet systematic process of creating structures of emergency medical aid has started. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. If it was not for the chronicle of Voivodeship Rescue Service Station in Rzeszów, obtaining the knowledge regarding the history and development of emergency medical aid, and then medical rescue services in Rzeszów and former Rzeszów Voivodeship - current Podkarpackie Voivodeship would be hindered or else impossible. The chronicle was created between 1967 and 1968 to the order of the then director of Voivodeship Rescue Service Station in Rzeszów Stanisław Widlarz. The author of this valuable chronicle was Piotr Kamiński, the administrative director of the station in Rzeszów, its long-time employee and co-founder of many poviat rescue service stations in the former area of Rzeszów Voivodeship. At present, the Voivodeship Rescue Service Station in Rzeszów implements tasks of the Emergency Medical Services (EMS). It boasts the most numerous medical rescue teams in Podkarpackie Voivodeship. Just like the day it was founded, the top priority for the station is saving human life and health. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method. The paper is based on the above mentioned chronicle of Voivodeship Rescue Service Station in Rzeszów, archive of Voivodeship Rescue Service Station in Rzeszów, web pages which served as sources of information on foundation, development and current operating and organization of the Voivodeship Rescue Service Station in Rzeszów and its vicinity, as well as bibliography on history of Rzeszów and its vicinity. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Due to the information shortage concerning the history records of rescue service in Rzeszów, the authors of this paper made the first attempt to publish the vital information on the history of medical rescue service in Rzeszów region.